2005
DOI: 10.1007/s00415-005-0967-9
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of differential diagnosis in neurological patients with livedo reticularis and livedo racemosa

Abstract: Livedo is a cutaneous sign of striking violaceous netlike patterned erythema of the skin. This dermatological phenomenon is of special interest in the differential diagnosis in neurological patients. In 1907 Ehrmann distinguished two different patterns of livedo: the pathological livedo racemosa and the physiological livedo reticularis. Despite important clinical differences, in the English language literature the heading livedo reticularis is still used for all types of livedo. A literature review about the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 90 publications
2
62
1
7
Order By: Relevance
“…Livedo was noted before cerebrovascular events in more than half of the patients with Sneddon syndrome in two reported studies. 20,23 In our series, a statistically significant association between histopathological necrotizing vasculitis in the skin biopsy specimen and ischemic cerebrovascular events was found among patients in whom livedo was noted. These findings indicate that histopathological cutaneous necrotizing vasculitis may be a useful parameter to define the risk of ischemic cerebrovascular events.…”
Section: Livedo Racemosasupporting
confidence: 48%
“…Livedo was noted before cerebrovascular events in more than half of the patients with Sneddon syndrome in two reported studies. 20,23 In our series, a statistically significant association between histopathological necrotizing vasculitis in the skin biopsy specimen and ischemic cerebrovascular events was found among patients in whom livedo was noted. These findings indicate that histopathological cutaneous necrotizing vasculitis may be a useful parameter to define the risk of ischemic cerebrovascular events.…”
Section: Livedo Racemosasupporting
confidence: 48%
“…There are no speciWc criteria for diagnosis of SS; therefore, the clinical observation of livedo reticularis and neuroradiological conWrmation of [4,12], are key factors in the diagnosis of SS [11]. In this study, arterial hypertension was the only risk factor for cerebrovascular disease found to be more prevalent in patients with PAPS with SS than in those with PAPS without SS, in agreement with observations made in previous studies [4,11].…”
Section: Discussionsupporting
confidence: 94%
“…The cause of SS is still unclear, its aetiopathology remains controversial, and its association with antiphospholipid antibodies is under debate [3,12].…”
Section: Discussionmentioning
confidence: 99%
“…Due to our clinical experience the spectrum of differential diagnoses in patients admitted to us for second opinion in evaluation of PCNSV consists of noninflammatory vasculopathy due to arteriosclerosis [18] or drugs [33], Moyamoya disease and syndrome [24] and Sneddon´s syndrome [20][21][22]25] as well as atypical cases of multiple sclerosis [19]. One other important differential diagnosis of PCNSV is bacterial endocarditis [4], because both conditions may present with similar clinical and auxiliary findings but effort a different treatment regimen [5].…”
Section: Discussionmentioning
confidence: 99%